THE EFFECT OF PHYSICAL EVIDENCE, PRICE DISCOUNT, AND PRODUCT DIVERSITY ON IMPULSE BUYING CONSUMERS OF SYARAH BAKERY BENGKULU - Yusuf, Mariano; Puspita, Veny; Waliamin, Janusi (Jurnal Signaling, 2024)
To find out how much influence physical evidence has on the impulse buying of Syarah Bakery Bengkulu consumers, To find out how much influence price discounts have on the impulse buying of Syarah Bakery Bengkulu consumers, To find out how much influence product diversity has on the impulse buying of Syarah Bakery Bengkulu consumers, To find out how much The influence of physical evidence, price discounts, and product diversity on the impulse buying of Syarah Bakery Bengkulu consumers. This research method is exploratory. Exploratory research, or also called exploratory research, is a research approach that aims to find information about a topic/problem that is not yet fully understood by a researcher. Exploratory research does not require a specific hypothesis or theory. The researcher only prepared several questions as a guide to obtain primary data in the form of information, information, as initial data needed. Based on the results of Physical Evidence (X1), it has an effect on consumer impulse buying (Y) Syarah Bakery Bengkulu City with a tsig value of 0.000, thus Ho is rejected and Ha is accepted, which means that variable X1 influences consumer impulse buying (Y). Price Discount (X2) influences the impulse buying (Y) of Syarah Bakery, Bengkulu City with a tsig value of 0.001, thus Ho is rejected and Ha is accepted, which means that the variable X2 influences consumer impulse buying (Y). Product diversity (X3) influences the impulse buying (Y) of Syarah Bakery, Bengkulu City with a tsig value of 0.002, thus Ho is rejected and Ha is accepted, which means that the variable X2 influences consumer impulse buying (Y). Physical Evidence, Price Discount and product diversity together influence consumer impulse buying with a value of Fsig α where Fsig is 0.000